2016
DOI: 10.1186/s13049-016-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of suspected acute heart failure dyspnea in the emergency department: results from the French prospective multicenter DeFSSICA survey

Abstract: BackgroundAn appropriate diagnostic process is crucial for managing patients with acute heart failure (AHF) in emergency department (ED). Our study aims to describe the characteristics and therapeutic management of patients admitted to the ED for dyspnea suspected to have AHF, their in-hospital pathway of care and their in-hospital outcome.MethodsConsecutive patients admitted in 26 French ED for dyspnea suspected to be the consequence of AHF, prior to in hospital diagnostic test, were prospectively included at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…We believe that the settings in which predictors of outcome are studied is highly relevant for AHF. Indeed, as previously demonstrated by our group in the DEFSICA study, 3 patients admitted for acute dyspnoea in the ED are often older, sicker and have a higher degree of associated comorbidities as well as associated acute dyspnoea aetiology than patients admitted in cardiology wards. Importantly, only a small proportion of our population was admitted to a cardiology ward after ED stay (<20%), clearly underscoring the selection bias derived from data acquired solely in cardiology departments.…”
Section: Discussionsupporting
confidence: 55%
“…We believe that the settings in which predictors of outcome are studied is highly relevant for AHF. Indeed, as previously demonstrated by our group in the DEFSICA study, 3 patients admitted for acute dyspnoea in the ED are often older, sicker and have a higher degree of associated comorbidities as well as associated acute dyspnoea aetiology than patients admitted in cardiology wards. Importantly, only a small proportion of our population was admitted to a cardiology ward after ED stay (<20%), clearly underscoring the selection bias derived from data acquired solely in cardiology departments.…”
Section: Discussionsupporting
confidence: 55%
“…As such, the data are primarily applicable to the French population, although wider extrapolation is possible due to coherences with similar studies in other geographical regions. The overall DeFSSICA study data are presented elsewhere10 and the present subanalysis reports real-life data from subgroups of patients with AHF with or without concomitant renal dysfunction, based on a CrCl threshold of 60 mL/min. The results show that AHF admissions to EDs are often associated with renal impairment, with almost two-thirds of AHF admissions having CrCl ≤60 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective, multicentre study in patients presenting with suspected HF dyspnoea in 26 EDs in academic, community and regional hospitals (the DeFSSICA study) for which the rationale and design are reported elsewhere 10. Written information regarding the objectives of the survey was provided to all patients prior to their inclusion according to French law.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is likely room for improving the diagnostic approach to AHF from widely available routine tools including chest radiography (CXR). CXR is a fast and inexpensive method performed systematically in the ED in patients with acute dyspnea [10][11][12]. It is the first-line diagnostic imaging modality advocated in current guidelines [13].…”
Section: Introductionmentioning
confidence: 99%